The changes in conformation of (Na+ K+)-ATPase from rat brain membranes are accompanied by changes of protein segment movements in the nanosecond range - Amler, E; Teisinger, J; Svoboda, P; Vyskocil, F (Physiologia Bohemoslovaca, 1988)
Differential polarized phase fluorometry of fluorescein-5-isothiocyanate (FITC) showed that the activation of (Na,K)-ATPase in crude plasma membranes from rat brain by 10 mmol.l-1 K+ and 100 mmol.l-1 Na+ significantly increased the rotational relaxational rate (R) of enzyme-bound FITC. This increase was blocked by both ouabain (0.1 mmol.l-1) and vanadate (0.1 mmol.l-1). In the absence of ATP, R was increased less after adding of 10 mmol.l-1 K+ to the membranes. The shifts in the nanosecond movements of the protein segments measured as R during the activation of (Na,K)-ATPase suggest that this type of movement might be of some functional importance.
Keywords: mozek; Brain; zvířata; buněčná membrána; Rats; thiokyanatany; Protein Conformation; fluoresceiny; Cerebral Cortex; Fluorescein-5-isothiocyanate; Fluorescent Dyes; sodíko-draslíková ATPasa; konformace proteinů; Thiocyanates; inbrední kmeny potkanů; Cell Membrane; fluorescein-5-isothiokyanát; mozková kůra; Kinetics; Spectrometry, Fluorescence; krysa rodu Rattus; kinetika; Rats, Inbred Strains; Animals; fluorescenční barviva; Fluoresceins; fluorescenční spektrometrie; Sodium-Potassium-Exchanging ATPase